Assessment of the fibre orientation factor in SFRC slabs - Ana Blanco-Alvarez; Pablo Pujadas; Albert De la Fuente; Sergio Pialarissi-Cavalaro; Antonio Aguado (2014)
The design of steel fibre reinforced concrete (SFRC) structures is evolving towards a new approach that uses correction factors to consider differences between the small-scale characterisation specimens and the real-scale elements. Recently, the Model Code 2010 proposed an orientation factor (K) that accounts for the effects of the orientation in the structural response of elements. The present study focuses on the identification of this factor in SFRC slabs with different dimensions. For that, flexural tests on real-scale slabs were conducted and the fibre orientation was assessed with an inductive method. A finite element analysis showed the differences between the experimental curves and the prediction of the Model Code without considering K. Based on the results obtained, a range of values is proposed for K and validated. This study sheds light on possible modifications that this philosophy of design might require to better reproduce the behaviour of slabs.